Cardiovascular disease risk factors among auto rickshaw drivers of Mangaluru - Gupta, Animesh; Adhikari, Shubhankar (International Journal Of Community Medicine And Public Health, 2018)
Background: Cardiovascular diseases are considered as one of the leading causes of death in developed countries as well as in developing country. Auto rikshaw drivers are at more risk of developing cardiovascular disease because of harmful lifestyle like irregular eating habits, addictions, insufficient sleep, stressful occupational conditions and sedentary lifestyle. Methods: Cross sectional descriptive study was conducted among auto rickshaw drivers working in Mangaluru. Data was collected regarding risk factors and general physical examination, anthropometric examination, systemic examination was done. Laboratory investigation was done for diabetes and dyslipidemia. Results: The mean age of study participants was 42.75±10.26. The prevalence of physical inactivity, hypertension and diabetes were 70%, 29.6% and 14.2% respectively. Conclusions: Physical inactivity, obesity, tobacco consumption and dyslipidemia were the major risk factors for cardiovascular disease.